Pengalaman Penggunaan Microsoft Copilot dalam Otomatisasi Pekerjaan: Studi pada Karyawan Perusahaan Teknologi - Simarmata, Yohana Vanessa Rebecca; Fiona, Fiona; Indiani Husnita, Sri Rezeky; Irwansyah, Irwansyah (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
The emergence of artificial intelligence (AI) technologies such as Microsoft Copilot has brought significant changes to professional work practices, particularly in the automation of daily tasks. This study aims to: (1) explore employees' motivations for using Microsoft Copilot; (2) identify the forms of gratification experienced by users; and (3) understand the subjective experiences and personal meanings constructed using this technology. This research employs a qualitative approach with a descriptive case study design. Data were collected through semi-structured interviews with employees at a technology company and analyzed through open, axial, and selective coding. The findings reveal that work efficiency, ease of information access, and the drive for creative exploration are the main motivations for using Copilot. The study also uncovers various forms of gratification such as delegated knowing, linguistic empowerment, paradox of agency, and localization gratification, reflecting the complex interaction between humans and AI in digital workspaces. This research contributes to the development of the Uses and Gratifications theory in the context of AI-based technologies and offers practical insights for organizations seeking to integrate AI more effectively into the workplace.